LITHOLOGIC FEATURES OF MIDDLE EOCENE DEPOSITS OF THE BLACK SEA NORTH-WESTERN SHELF - REVER, V.B. (Institute of Geological Sciences, NAS of Ukraine, 2012)
The territory of researches include the Black sea north-western shelf, where Middle Eocene deposits are opened by numerous wells on seventeen structures. In connection with small coring deposits of Middle Eocene age are studied insufficiently. On a basis of lithologic studying of this complex three types of sections are distinguished: carbonate, terrigenous-carbonate and terrigenous. Areas of dominate development of terrigenous (Odessko-Bezimenna) and carbonate deposits (Gamburtsivsky, Shmidtivsky, Olimpic) are established. Petrography features of the rocks are studied. These results are a base for geology paleoceanographic reconstructions of the Carpathian Black sea segment of Tethys ocean. They allow correlating Tethydian Eocene deposits developed in adjoining regions of the East European platform and Carpathian orogene.